Protective Effects of Niclosamide Ethanolamine Against Testosterone-Induced Benign Prostatic Hyperplasia in Rats - Jasim, Ali Hussein; Abu-Raghif, Ahmed Rahmah; Hussein, Zeena Ayad (Drug Research, 2025)
Benign prostatic hyperplasia is a common urological condition in aging men. The anthelmintic agent niclosamide ethanolamide exhibits a wide range of pharmacological activities. This study aimed to evaluate the protective effect of niclosamide ethanolamide in testosterone propionate-induced benign prostatic hyperplasia in rats along with elucidating the probable mechanism of action by investigating the influence on PPAR-γ and Wnt/β-catenin. 40 male Wistar rats were divided randomly into 4 groups. The healthy (control) group, received daily oral and subcutaneous administration of the vehicle. The Induced (TP) group, received only a daily dose of testosterone propionate 3 mg/kg, SC for 28 days. The treated groups (TP+FIN) and (TP+NE), received a concomitant administration of a daily dose of testosterone propionate along with finasteride 5 mg/kg/day and niclosamide ethanolamide 50 mg/kg/day respectively through oral gavage. Animals were euthanized on day 30 of the experiment and prostate tissue samples were collected to evaluate prostate index, prostate hyperplastic markers by ELISA, and gene expression by RT-qPCR. Results revealed that niclosamide ethanolamide significantly reduced prostate index compared to the induced (TP) group (P<0.0001). The agent nearly normalized BPH markers including 5α-reductase type-2 enzyme, dihydrotestosterone, and PCNA compared to the induced (TP) group (P<0.0001). The agent reduced the tissue level of β-catenin while elevating PPAR-γ to control levels (P<0.05). The current study revealed that NE can help prevent BPH in rats by upregulating the PPAR-γ receptor and inhibiting the Wnt pathway.
Keywords: Benign prostatic hyperplasia; Testosterone propionate; PPAR-gamma; Niclisamide ethanolamide; Beta-catenin; 5α-reductase